Koordinasi Tim Pora Dalam Pengawasan Tenaga Kerja Asing Legal Tenaga Pendidik Di Kota Medan - Sabrina Sabrina; Siti Hazzah Nur, R (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The PORA team is a team consisting of several agencies that have duties and functions related to the presence and activities of foreigners. The coordination between the PORA Team and the Manpower Office is to strengthen the supervision of foreign workers from administration to field supervision, but internally, the PORA Team still has problems. This study aims to identify and describe the coordination of the PORA Team in the supervision of legal TKA educators in Medan City. The research method used is descriptive qualitative method. The results of the study indicate that coordination in the supervision of foreign workers requires an approach between members and inter-institutional meetings. In the agency's business indicators, the coordination of the PORA Team caused internal problems due to a lack of understanding of the main tasks and functions of the members. In the unit of action indicator, the existence of sectoral egos such as the Manpower Office acts by itself in the supervision of foreign workers. On the indicators of shared goals, the agencies that are members of the PORA Team designate Immigration as their leading sector. However, there are findings in the field, that there is an agency under the auspices of the Medan City Government which forms a Foreigner Monitoring Team.